Хмонг мəдениетінің демонологиясы. Демонология в культуре хмонгов. - Saikeneva, D. K. (Journal of Oriental Studies, 2016)
Demonology in hmong minority’s cultureIn this article author considers presence of mythology in the modern life of traditional society, and transformation of archaicfears to modern phobias. The article represents analysis of night mare’s archetype in Hmong’s culture. Author considers necessity ofreconstruction traditional society’s mythology, which give understanding of habits and thinking of traditional groups. This examplecovers post-war situation in the U.S.A. There are representatives of Hmong’s minority faced with revival of primal fear before nightmare in their consciousness. In conclusion, the author infers need for integrated study of mythology, for a more adequate interpretationof the changes in the life of traditional societies.Thus, in the article, the author focuses on the reconstruction of the mythology, uses typological parallels from other traditionalmyths and traditional beliefs, which helps to establish the spatial, social and cultural characteristics of traditionsand transformationof thearchetypes in the world. The author contributes to the understanding of the role of tradition in modern Hmong culture.